Quantitative measurements and modeling of industrial formaldehyde emissions in the Greater Houston area during campaigns in 2009 and 2011. Issue 7 (9th April 2014) - Johansson, John K. E.; Mellqvist, Johan; Samuelsson, Jerker; Offerle, Brian; Moldanova, Jana; Rappenglück, Bernhard; Lefer, Barry; Flynn, James
Abstract: A sensitive Mobile differential optical absorption spectroscopy (DOAS) system with real‐time evaluation capability and HCHO detection limit of 3 ppb over 100 m has been developed. The system was operated together with a Solar Occultation Flux system for large‐scale vertical flux measurements of HCHO, NO2, SO2, and VOCs in the Houston‐Galveston‐Brazoria area during two studies, in 2009 (Study of Houston Atmospheric Radical Precursors campaign) and in 2011 (Air Quality Research Program study). Both in 2009 and 2011, HCHO plumes from five separate local sources in Texas City, Mont Belvieu, and Houston Ship Channel (HSC) were repeatedly detected using Mobile DOAS with emissions varying between 6 and 40 kg/h. In many cases significant alkene emissions were detected simultaneously with the HCHO plumes. Furthermore, in 2011 two additional sources were observed in Texas City and in HSC, with 10 kg/h and 31 kg/h HCHO, respectively. A plume chemistry model was applied to 13 cases to investigate whether the detected HCHO was emitted directly from the industries or was produced by photochemical degradation of VOCs. The model results showed that on average 90% of the detected HCHO was of primary origin and the photochemical production contributed more than 10% in only three cases. Based on the repeatability, it is likely that the most significant HCHO sources in the area are included in this study with an overall emission of 120 kg/h. On a regional scale, this emission is small compared to the secondary HCHO formed from oxidation of reactive VOCs emitted from the same industries, estimated to be an order of magnitude higher. Key Points: Total HCHO emissions are measured from industrial sources in Houston Industrial HCHO emission plumes are photochemically modeled Primary emissions generally dominate HCHO emissions on local spatial scales